Bounded Doubly Close-to-Convex Functions - Dorina Răducanu (Abstract and Applied Analysis)
We consider a new class CC(α,β) of bounded doubly close-to-convex functions. Coefficient bounds, distortion theorems, and radius of convexity for the class CC(α,β) are investigated. A corresponding class of doubly close-to-starlike functions S*S(α,β) is also considered.